Faktor Predisposisi Dan Pemungkin Perilaku Penggunaan Kondom Padapelanggan WPS Di Semampir Kediri - Shinta Kristianti (coba, 2016)
Transmission of HIV-AIDS in Indonesia is growing fast, one of the triggers are due to risky sexual behavior, including sexual behavior in FSW’s clients. This study aimed to analyze the factors that influence the behavior of condom use on the FSW’s clients in Semampir Kediri. This study used quantitative methods to the design of explanatory research with cross sectional approach. A triangulation of qualitative data used to support the results of quantitative analysis were excavated from WPS and pimps as a cross check answers FSW’s clients, the means used was to in-depth interviews and FGDs (Focus Group Discussion) on the FSW and pimps. Sample size was 66 people. Univariate data analysis, with chi-square bivariate and multivariate logistic regression. Results showed most respondents (71.2%) behave consistent in using condoms.Variables related to condom use behavior in FSW were knowledge, perception of vulnerability, severity perceived, benefits perceived, barriers perceived and perceived ability to self (self-efficacy), the availability of condoms, condom regulation, support of friends and support of FSW. Support of friend was the most influential variable on the practice of using condoms to FSW’s clients and the OR value was 19.218. Key words: female sex workers (FSW), FSW’s clients, condom, consistent